2019
DOI: 10.3390/insects10090266
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Locality and Host Plant on the Body Size of Aeolothrips intermedius (Thysanoptera: Aeolothripidae) in the Southwest of Poland

Abstract: Aeolothrips intermedius is a thrips predator often found in phytocoenoses worldwide. Both the adults and larvae of this species prey on small invertebrates, including phytophagous species from Thysanoptera group. The aim of this study was to determine the morphological variability of the A. intermedius relative to the locality and, indirectly, to the species of host plant. Insects were collected from five localities in southwest Poland and five different host plants. For each of the sexes, six morphometric fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…In this study, we were inspired by the strategy of immune-related gene pairing and attempted to construct a reasonable model with two-lncRNA combinations and did not adopt their exact expression levels in the signature for the first time. 25 First, we retrieved raw data of lncRNAs from TCGA, performed a differential co-expression analysis to classify DEirlncRNAs, and validated lncRNA-pairs using an improved method of cyclically single pairing along with a 0-or-1 matrix. Second, we performed univariate analysis combined with a modified Lasso penalized regression including procedures of cross validation, multi-times repeat, and random stimulation to determine DEirlncRNAs pairs.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we were inspired by the strategy of immune-related gene pairing and attempted to construct a reasonable model with two-lncRNA combinations and did not adopt their exact expression levels in the signature for the first time. 25 First, we retrieved raw data of lncRNAs from TCGA, performed a differential co-expression analysis to classify DEirlncRNAs, and validated lncRNA-pairs using an improved method of cyclically single pairing along with a 0-or-1 matrix. Second, we performed univariate analysis combined with a modified Lasso penalized regression including procedures of cross validation, multi-times repeat, and random stimulation to determine DEirlncRNAs pairs.…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of volatiles or secondary metabolites, the food quality greatly influences the performance of thrips [33]. Plant nutrients can affect the feeding and reproduction of insects, and the adaptability of insects to their hosts, such as Aeolothrips intermedius, Thrips palmi, and Thrips obscuratus [33][34][35][36][37]. In fact, studies have shown that pollen has a substantial influence on the survival rate and oviposition of F. occidentalis [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of this technique is that it is not dependent on the expression levels of the gene signature. 28 …”
Section: Discussionmentioning
confidence: 99%
“…The advantage of this technique is that it is not dependent on the expression levels of the gene signature. 28 In this study, we downloaded raw datasets of lncRNAs from TCGA and adopted a differential co-expression analysis to pair IRlncRs. Then, IRlncRs-pairs were identified using an improved method of cyclically single pairing along with a 0 or 1 matrix.…”
Section: Discussionmentioning
confidence: 99%